Alcohol's Harm to Others: Does the Drinking Location Matter?. (24th August 2021) - Moan, Inger Synnøve; Brunborg, Geir Scott
Abstract: Background: In order to curb alcohol's harm to others, it is important to identify the contexts where people experience such harm. Objectives : To examine whether frequency of drinking in four different locations was associated with increased likelihood of experiencing harm from others' drinking. Methods : Data stem from surveys conducted in the five Nordic countries in 2015 ( N = 7065, aged 18–64 years) as part of the European Union's Joint Action on Reducing Alcohol Related Harm (RARHA). Three types of harm from others' drinking in the past 12 months were measured: verbally abused by, harmed physically by, and experienced a serious argument with someone who had been drinking. Respondents also reported frequency of drinking in their own home, in others' homes, in a pub/bar/club/restaurant, and outdoors the past 12 months. Results : Country-pooled adjusted analyses showed that higher frequency of drinking in pubs/bars/clubs/restaurants, outdoors and in someone else's home was associated with increased likelihood of experiencing all three harms. Frequent drinking in one's own home was weakly associated with experience of harm. Women, young individuals, respondents without tertiary level of education and individuals who reported drinking almost daily were at increased risk of experiencing harm from others' drinking. Conclusions : Frequent drinking on licensed premises and outdoors was most clearly associated with experiencing harm from others' drinking, suggesting that these are important arenas for preventive efforts. Women, young individuals, those with low educational level and the most frequent drinkers are important target groups for preventive efforts.